Socio-Economic Status of Samarinda City Community in Political Participation - Muhammad Noor; Rita Kala Linggi (Budapest International Research and Critics University, 2021)
Along with the ongoing democratic process, Indonesia also showed ability in the democratic process. All elections conducted through a series of systems of government and politics, directly ask for the participation of the public. Therefore, there needs to be research to find out the participation of the people of Samarinda City with socio-economic status to political participation. This research aims to find out the Socio-Economic Status of Samarinda city community in political participation. The subjects of the study numbered 180 respondents taken on an accidental basis. The data collection method used is a political participation questionnaire. The data analysis technique used in this study is a descriptive analysis regarding the socio-economic status of the people of Samarinda City in participating in politics. The results obtained from this study found that overall political participation in society was low. As for the categorization score on the socio-economic status of the people of Samarinda City who have a low socioeconomic status in low political participation, on the socio-economic status of Samarinda city people who have a moderate socioeconomic status in low political participation, and on the socio-economic status of Samarinda city people who have a high socioeconomic status in low political participation.